COMPUTER STORE INVENTORY SYSTEM DESIGN USING VISUAL BASIC 6.0 XYZ - Toni Anggono (Jurnal Manajemen Informatika, 2010)
Progress in the field of computers at this time was very fast in the community. Benefits ofcomputerization are not only enjoyed by large companies but also by the Computer Store and evenindividuals. One progress computer is a database processing system.Computerized data processing is very helpful Computer Stores in processing the data, especially datawhich is quite a large item. Computerization is part of a major activity of Computer Stores in progressTokoKomputer benefits. Computerization will also show the performance of the shop to customers thatwill give the impression keprofesionalismean Shop by customers.Performance of the Computer Store can not be separated from data and information quickly andaccurately. Search and exchange information in the Computer Stores became faster and will certainlyreduce the waste of working time in the Computer Store.